Encyclopaedia Britannica ultimate reference suite 2005 CD - Encyclopaedia Britannica Inc. (Chicago : Encyclopaedia Britannica India P. Ltd., 2005)
Contains over than 100,000 arcticles, world atlas with 2,514 maps, dictionary, thesaurus, web sites link and Merriam-Webmaster's dictionary.
System requirements for windows : Microsoft windows 98 SE, 2000,me,xp, pentium 350 mhz or faster processer, 256 MB Ram, 550 Mb free hard-disk space, CD-rom drive, 800x600 resolution, 16-bit colour, mouse, sound card and speaker.
System requirements for Macintosh : Mc os 10.3, imac or G3 350 mhz or faster processor, 256 mb ram, 550 mb free hard-disk space, cd-rom drive, 800 x 600 resolution, mouse, sound card and speakers.
Keywords: Encyclopedias and dictionaries; Electronic encyclopaedia